2012
DOI: 10.1021/jf303936j
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Butachlor by Rhodococcus sp. Strain B1 and Purification of Its Hydrolase (ChlH) Responsible for N-Dealkylation of Chloroacetamide Herbicides

Abstract: Rhodococcus sp. strain B1 could degrade 100 mg/L butachlor within 5 days. Butachlor was first hydrolyzed by strain B1 through N-dealkylation, which resulted in the production of butoxymethanol and 2-chloro-N-(2,6-dimethylphenyl)acetamide. Butoxymethanol could be further degraded and utilized as the carbon source for the growth of strain B1, whereas 2-chloro-N-(2,6-dimethylphenyl)acetamide could not be degraded further. The hydrolase designated ChlH, responsible for the N-dealkylation of the side chain of buta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…The results showed that the degradation of metamitron by the isolate MET was significantly ( p  ≤ 0.05) faster at pH 7.0 than at pH 5.0 and 9.0, implying that microbial degradation was a pH-dependent process202122. Similarly, Liu et al 23. reported that the optimal pH for the degradation of the herbicide butachlor by Rhodococcus sp.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The results showed that the degradation of metamitron by the isolate MET was significantly ( p  ≤ 0.05) faster at pH 7.0 than at pH 5.0 and 9.0, implying that microbial degradation was a pH-dependent process202122. Similarly, Liu et al 23. reported that the optimal pH for the degradation of the herbicide butachlor by Rhodococcus sp.…”
Section: Resultsmentioning
confidence: 88%
“…Some researchers also found that temperature had a significant influence on the biodegradation of triazinone herbicides and other herbicides92526. Liu et al 23. reported that the optimal temperature for the degradation of chloroacetamide herbicides by Rhodococcus sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Article sp., 15 Acinetobacter sp., 28 Mycobacterium sp., 14 and Sphingobium sp. 14,29 Members of Bacillus are widespread in nature and play an important role in the ecosystem.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…In general, the major methods for butachlor degradation include dechlorination, hydroxylation, dehydrogenation, debutoxylation, debutoxymethylation, N-dealkylation, Odealkylation, cyclization, etc. 35−37 Liu et al 15 reported that butachlor was only hydrolyzed by strain B1 through Ndealkylation, which resulted in the production of butoxymetha- …”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%